Post‑infectious ST elevation myocardial infarction following a COVID‑19 infection: A case report. Issue 2 (18th October 2021) - CECCARELLI, MANUELA; MARINO, ANDREA; COSENTINO, FEDERICA; MOSCATT, VITTORIA; CELESIA, BENEDETTO MAURIZIO; GUSSIO, MARIA; BRUNO, ROBERTO; RULLO, EMMANUELE VENANZI; NUNNARI, GIUSEPPE; CACOPARDO, BRUNO SANTI
No abstract available